DIGITAL TECHNOLOGIES IN SOURCE STUDY AND HISTORIOGRAPHY: EXPERIENCE OF APPLYING THE JACQUES KAYSER METHOD IN CAUCASUS STUDIES - Zurtova, Anzela Arikovna; Kuz'minov, Petr Abramovic; Kazarov, Artur Gusmanovic; Tahuseva, Inna Sarabievna (History, Archeology and Ethnography of the Caucasus, 2024)
This paper examines the use of digital technologies in historical research, focusing on the application of content analysis methods in studying historical and historiographic sources. The authors investigate the fundamental principles, stages, and mechanisms of content analysis, considering the combined use of quantitative and qualitative approaches in textual analysis. They explore the method’s capacity to reveal extra-textual realities shaped by the socio-political context of the era and the author’s worldview. The paper identifies key digital methods for conducting content analysis in social sciences and humanities research (TextAnalyst 2.0, XML, Crawdad Desktop, INTEXT, Kwalitan, Protan, Yoshikoder, etc.) and examines the potential of cognitive models in source study. Content analysis is intrinsically linked to the linguistic characteristics of the source text. The initial stage typically involves creating a sample of frequently used language units and categories, which form the basis of the analysis. Subsequently, the semantic units of the selected concepts are recorded and interpreted, transforming quantitative indicators into a qualitative understanding of the subject under study. The authors highlight the main advantages and disadvantages of content analysis, noting the primary challenge in its implementation: the difficulty of formalizing historical or historiographical source texts due to the inherent flexibility of language structures and their connection to individual worldviews and unique phenomena. The article presents a case study applying a specific type of content analysis developed by French scholar Jacques Kayser in the field of Caucasus studies. This method was used to analyze articles in the journal “Otechestvennye zapiski” focused on North Caucasus history, providing a scaled assessment of publications about mountain peoples. The authors argue that the future prospects of content analysis in historical and historiographical research depend on improving mechanisms for combining quantitative and qualitative approaches.